2022
DOI: 10.1186/s40249-022-00993-x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the viruses belonging to the order Bunyavirales in China

Abstract: Background Viral pathogens belonging to the order Bunyavirales pose a continuous background threat to global health, but the fact remains that they are usually neglected and their distribution is still ambiguously known. We aim to map the geographical distribution of Bunyavirales viruses and assess the environmental suitability and transmission risk of major Bunyavirales viruses in China. Methods We assembled data on all Bunyavirales viruses detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…A study reported that more than 200 cases of CCHFV had occurred in China with more than 50 deaths as of 2003 ( Fereidouni et al, 2023 ). A population serologic study for CCHFV reported that seropositive cases could be found in northeastern, northwestern, and southern China, but no cases of human infection had been detected outside of XUAR ( Teng et al, 2022 ). Hyalomma spp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study reported that more than 200 cases of CCHFV had occurred in China with more than 50 deaths as of 2003 ( Fereidouni et al, 2023 ). A population serologic study for CCHFV reported that seropositive cases could be found in northeastern, northwestern, and southern China, but no cases of human infection had been detected outside of XUAR ( Teng et al, 2022 ). Hyalomma spp.…”
Section: Resultsmentioning
confidence: 99%
“…TBVs of the family Nairoviridae were distributed in most parts of XUAR and northeastern China ( Figure 2A ). Many provinces in China had human serologic evidence suggesting the presence of CCHFV, but the provinces where CCHFV was detected in ticks was only XUAR, Yunnan and Inner Mongolia Provinces ( Teng et al, 2022 ). CCHFV was mainly distributed in the grass-covered areas around the Tarim Basin and the Tianshan Mountains in XUAR.…”
Section: Resultsmentioning
confidence: 99%
“…Crimean Congo hemorrhagic fever (CCHFV), virus transmission, and Arenaviridae in #5 virus hemorrhagic fever. Teng et al ( 45 ) evaluated the environmental suitability and transmission risk of major Bunyavirales viruses in China by mapping the geographical distribution of all 89 Bunyavirales viruses reported in China from January 1951 to June 2021, and highlighted that Hantaviruses, Dabie bandavirus , and CCHFV had the severest disease burden. Two viruses, CCHFV and Rift valley fever virus (RVFV), may occur in local area outbreaks in China.…”
Section: Discussionmentioning
confidence: 99%
“…The CCHF virus was detected among ticks of sheep and camels in the Inner Mongolia region of China ( 43 ). From 1951 to 2021, only 447,848 cases were reported to be infected from bunyavirales viruses, and CCHFV, along with three other viruses, was reported to cause the most disease burden ( 44 ).…”
Section: Pattern Of Distribution In Asian and Middle Eastern Countriesmentioning
confidence: 99%